K Era Post-truth dan Perilaku Self-diagnosis: Era Post-truth dan Perilaku Self-diagnosis - Rawis, Daniel; Sitorus, Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
The era of post-truth, marked by the spread of false information that has created an environment in which objective truth is often threatened and replaced by narratives that match individual beliefs and emotions. Self-diagnostic behavior is increasingly emerging as the ability of information independence, where individuals tend to find out about their own health conditions through social media without professional consultation. Post-truth phenomena relate to self-diagnostic behavior where there are factors such as information literacy, social media, and technology that influence post-true and self-diagnosis. This paper explores the relationship between the post-truth era and self-diagnostic behaviour, investigating how the dissemination of unverified information affects the individual's decision to seek and receive medical diagnosis independently. This paper is expected to provide insight into the dynamics of the post-truth era in the context of health and identify efforts that can be taken to improve information literacy and sustainability of self-diagnostic behaviour in society.